Influence of sowing date and age of okra crop on the incidence of whitefly, Bemisia tabaci and Okra yellow vein mosaic virus - Manju, K P; Lakshmi, K Vijaya; Babu, B Sarath; Anitha, K (Indian Journal of Plant Protection, 2020)
A field trial was conducted to determine the effect of sowing dates and age of okra crop on the population build-upo f whitefly, Bemisia tabaci and subsequent Okra yellow vein mosaic virus (OYVMV) incidence. Okra variety, â€œArka Anamikaâ€ was sown at four different dates viz., 1st March, 15th March, 1st April and 15th April during Summer 2015 and 2016. Among the different dates of sowing, 1st April sown crop was infested severely by whiteflies and OYVMV, while early sown, 1st March and 15th March plots suffered significantly less infestation in both the years. Age of the crop also played a significant role on whitefly population and OYVMV incidence. Significantly lowest population of whiteflies was recorded at the beginning and end of the crop season at 19 and 90 days age of the crop (1.64 and 1.95/3 leaves, respectively) while, the highest population was recorded at 47 days age of the crop (8.88/3 leaves).The disease incidence started at 33 days age of the crop (7.5 %), and reached to a maximum infestation of 78.7 per cent at 90 days age of the crop i.e. at the end of crop season. Significantly lowest fruits (11.17 fruits/plant) and fruit yield (5102 kg/ha) were recorded from the D3 plot sown during 1st April, while D1 plot sown during 1st March ecorded the highest number of fruits (15.56 fruits/plant) and fruit yield (8370 kg/ha).